Supporting Workers and Communities: Recommendations to the Government of Alberta - Alberta. Advisory Panel on Coal Communities (Author) (Government of Alberta, 2017)
The report makes 35 recommendations focused on three areas: workers, communities and First Nations. Those regarding workers relate to income security and replacement, pension security, retraining and re-employment – and recommend a strong role for unions in planning and process.